PEMANFAATAN PEMASARAN MELALUI MEDIA SOSIAL OLEH UMKM DI ERA PANDEMI - Mira Veranita; Lukmanulhakim Almamalik; Sugiyanto Iksan (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
The restrictions imposed to prevent the spread of the Corona virus have greatly impactedvarious types of businesses, both large-scale businesses and MSMEs and have indirectlyforced business owners to make digital marketing, especially marketing through socialmedia, one of the business solutions in marketing their business. This study aims todetermine the use of social media as a marketing medium for MSMEs in the midst ofvarious restrictions due to the Covid-19 pandemic. The method used in this study is aqualitative descriptive method. The subjects of this study were MSME actors under theguidance of the Cooperatives and SMEs Service, Bandung Regency, which were selected asmany as 23 MSMEs using purvosive sampling technique. The research data was collectedcombining desk analysis and direct observation to MSME actors, interviews with keyrespondents from the Bandung Regency Cooperatives and SMEs Service, and digitalmarketing practitioners. The results of the study show that MSME actors have made socialmedia a marketing method in this pandemic era. Marketing using social media is usedbecause it is able to increase brand awareness, facilitate product feedback and marketingstrategies, build networks with consumers, suppliers and competitors, but in a moreconvenient and cost effective manner.